Perkembangan Teknik Kriptografi Modern: Dari Substitusi Klasik hingga Public-Key Encryption - Diva Nadya Putri; Divia Permata Sari; Maulidayana Maulidayana; Muksalmina Muksalmina; Muhammad Raihan Syafiq Lubis (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
The rapid development of digital technology has increased the need for secure information exchange, making cryptography a fundamental component of modern information security systems. In the early stages, cryptographic techniques were dominated by classical substitution ciphers, which are simple but vulnerable to various cryptanalysis attacks. This study aims to analyze the development of cryptographic techniques, from classical substitution ciphers to modern public-key encryption schemes. The research method used is a literature review by reviewing books, national journals, and international journals that discuss classical and modern cryptography. The results show that classical cryptographic methods are no longer adequate to meet current security needs because they have a limited key space and are vulnerable to attacks. In contrast, the emergence of modern cryptography, especially public-key encryption such as RSA and Diffie–Hellman, offers stronger security mechanisms, especially in the process of key distribution and secure communication over open networks. Based on these results, it can be concluded that public-key encryption plays a very important role in supporting the security of digital communications and has become the basis for various modern security applications.